Designing Japan a future built on aesthetics - Hara, Kenya 1958- (Japan library., 2018)
"'Designing Japan: A Future Built on Aesthetics' presents renowned designer Kenya Hara's vision of how his industry can support Japan in crafting a future founded on a unique philosophy of beauty as well as crowd-sourced wisdom from around the world. The book spans history from the beginnings of professional Japanese design in the sixteenth century to the impact of the 2011 Tohoku earthquake, but Hara's focus is the future. A master collaborator, meticulous organizer, and globally conscious innovator, he draws on more than three decades of participation in design work and exhibition curating, as well as deep professional interaction with creators from many fields. 'Designing Japan' serves as a foundation course on the essence of Japanese aesthetics while maintaining a practical approach to Japan's circumstances and future possibilities. Hara reveals the methods by which designers in Japan continue to work in tandem with government and industry to form publicly accessible aesthetic inquiries into how this island nation will proceed as its population ages, other nations take over manufacturing, and technology develops. Illustrations and examples recognize successful problem solving through design, proving that it is a living, changing industry that remains relevant not in spite of, but as a partner to, advancing technology"-- Unedited summary of book.